Species of the genus Allium L. of the western part of the Kyrgyz Alatau ridge: the current status and prospects of studying - Gemejiyeva, N.G.; Abdildanov, D.Sh.; Kudabayeva, G.M.; Vesselova, P.V.; Nelina, N.V.; Friesen, N.V. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The results of the assessment of the current state and prospects for the study of species of the genus Allium L. in the western part of the Kyrgyz Alatau ridge are presented. It was found that in the herbarium fund (AA) the most part (57 %) of specimen collections of Allium L. species falls on the periods from 1947 to 1960, further on descending 24 % of collections — in 1984–1985. The share of scattered collections is 12 %, the share of modern collections is insignificant (7 %). The preliminary list of studied species of Allium Kyrgyz Alatau is represented by 27 species. In 5 gorges of the western part of the Kyrgyz Alatau ridge, locations, phytocoenotic and altitudinal distribution of 7 species were revealed. Commercial thickets are formed by A. atrosanguineum (Kaskasu gorge) and A. longicuspis (Sugaty gorge). The identified species occur as part of herbaceous-grass, herbaceous-shrubby-cereal grass, petrophytic-herb-grass-shrub, petrophytic-tree-shrub communities and grow in the altitude range from 1200 to 3390 m above sea level. Allium caeruleum, A. caesium, A. karataviense, A. leptomorphum, A. longicuspis, A. margaritae are found in the low and middle mountains from 1170 to 1660 metres above sea level. The high-altitude species is A. atrosanguineum, occurring in the altitude range of 2520–3390 m above sea level. Maps of the locations and potential harvesting sites of the identified Allium species of the study region were compiled.
Keywords: Kyrgyz Alatau ridge; species diversity; genus Allium L.